Causes of Treatment Discontinuation in Retinal Diseases Treated with Intravitreal Injections - Abdin, Alaa Din; Barakat, Nicolas; Aljundi, Wissam; Abu Dail, Yaser; Munteanu, Cristian; Weinstein, Isabel; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose To determine the most common reasons for treatment discontinuation in patients with retinal diseases undergoing intravitreal injections (IVI s).Methods A retrospective study was conducted with all patients who underwent IVI therapy in our Department of Ophthalmology between January 2016 and January 2024. We investigated the reasons for therapy discontinuation, including non-persistence (declining therapy). Patients who declined therapy (non-persistence) were compared with the remaining patients to determine the potential factors responsible for their decision.Results The mean age of the 2218 patients (1155 women, 1063 men) who took part in the study was 77.6 ± 12.0 years. A total of 1029 patients (46.4%) achieved a dry macula in both eyes at the time of the study. Treatment was discontinued in 865 patients (39%) due to poor prognosis (visual acuity < 1.3 logMAR) (188, 8.4%), change to another medical centre (175, 7.9%), comorbid systemic diseases (128, 5.7%), loss of contact (128, 5.7%), financial problems with health insurance (13, 0.5%) or death (59, 2.6%), while 174 patients (7.8%) declined IVI therapy (non-persistence). Compared to the other patients, non-persistence patients were significantly older (76.2 ± 12 vs. 81.2 ± 11, p < 0.001), had significantly worse visual acuity (logMAR) at the last visit (0.50 ± 0.5 vs. 0.29 ± 0.2, p = 0.001), received a significantly higher number of IVI s (10 ± 11 vs. 14 ± 15, p < 0.001) and had a significantly higher proportion following the pro re nata treatment protocol (59% vs. 72%, p = 0.001).Conclusion The most common reason for treatment discontinuation was the poor prognosis, which related to the nature of macular diseases. Advanced age, higher number of injections, pro re nata protocol and reduced visual acuity during therapy were identified as factors that affected patient non-persistence to treatment.
Keywords: anti-VEGF therapy; retinal diseases; persistence; adherence; intravitreal injection